2022
DOI: 10.3389/fmars.2022.826810
|View full text |Cite
|
Sign up to set email alerts
|

Classifications and Characteristics of Marine Heatwaves in the Northern South China Sea

Abstract: The classifications and associated characteristics of marine heatwaves (MHWs) in the northern South China Sea (SCS) have been investigated. Based on the ratio of the area with MHWs to the total area of the northern SCS, the MHWs are divided into three categories, i.e., narrow coverage, moderate coverage, and wide coverage. Different kinds of MHWs (i.e., narrow coverage, moderate coverage, and wide coverage) contribute around 64, 28, and 8% to the total days with MHWs, respectively. Narrow coverage MHW scatters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The cross‐slope mesoscale perturbations in the upper layer could trigger topographical Rossby waves and drive the strong intraseasonal variability in the deep layer (Shu, Xiu, et al., 2016; Shu, Xue, et al., 2016; Shu et al., 2022; Wang et al., 2019, 2021). In addition, active cross‐slope water exchange induced by the mesoscale eddy in the northern SCS continental shelf edge is a main oceanic way that cools the water on the shelf, eventually resulting in the decay of marine heat waves (Wang et al., 2022). The mesoscale eddies have also been confirmed to generate cross‐slope volume transport between the continent and the deep‐sea basin (e.g., Chen et al., 2012; Wang et al., 2013; Yang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The cross‐slope mesoscale perturbations in the upper layer could trigger topographical Rossby waves and drive the strong intraseasonal variability in the deep layer (Shu, Xiu, et al., 2016; Shu, Xue, et al., 2016; Shu et al., 2022; Wang et al., 2019, 2021). In addition, active cross‐slope water exchange induced by the mesoscale eddy in the northern SCS continental shelf edge is a main oceanic way that cools the water on the shelf, eventually resulting in the decay of marine heat waves (Wang et al., 2022). The mesoscale eddies have also been confirmed to generate cross‐slope volume transport between the continent and the deep‐sea basin (e.g., Chen et al., 2012; Wang et al., 2013; Yang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Xisha area, outlined by the black box, exhibited a relatively low frequency of SSMHWs, with an average relative value of 0.96 and an annual frequency of approximately 1.56 Counts/Year (Figure 3A). The frequency of SSMHWs near the South China Sea Throughflow significantly exceeded that in the surrounding regions, with the highest incidence observed to the east of Hainan Island (Wang et al, 2022). The average relative duration of SSMHWs was 1.04, with an average duration of approximately 22.98 Days/Count (Figure 3B).…”
Section: Spatial Distribution and Temporal Variation Of Ssmhwmentioning
confidence: 96%
“…In recent years, coral reef degradation caused by temperature anomalies in the Xisha area has been increasing (Zuo et al, 2023). Previous studies indicated that SMHWs are more prevalent in the northern SCS, particularly east of Hainan Island and the continental shelf waters, compared to the weaker SMHWs in the Xisha area (Tan et al, 2022;Wang et al, 2022). However, SSMHWs in areas where SMHWs are weak may not be equally weak (Hu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerical ocean models have been employed for MHW forecasting in this region [18]. Seasonal variation of MHW has been shown to be important in marginal sea [19,20,21,22]. Meanwhile, seasonal variation of SST is significant in the ECS [20].…”
Section: Introductionmentioning
confidence: 99%